Association of symptom status, myocardial viability, and clinical/anatomic risk on long‐term outcomes after chronic total occlusion percutaneous coronary intervention. (2nd March 2021) - Song, Lei; Qiao, Shubin; Guan, Changdong; Bai, Yinxiao; Zou, Tongqiang; Wu, Fan; Shi, Yanpu; Xie, Lihua; Sun, Zhongwei; Dou, Kefei; Yang, Weixian; Brilakis, Emmanouil S.; et al.
Abstract: Objectives: This study aimed to examine the association of less‐certain indication of chronic total occlusion percutaneous coronary intervention (CTO‐PCI) with subsequent clinical outcomes. Background: The impact of patient symptoms, myocardial viability, and clinical and anatomic risk on long‐term outcomes is underdetermined. Methods: Consecutive patients undergoing CTO‐PCI at a large‐volume single center between 2010 and 2013 were included. Central adjudication was used to assess the appropriateness of three prespecified indications. The primary outcome was the 5‐year composite endpoint of death or myocardial infarction (MI). Results: Of 2, 659 patients with 2, 735 CTO lesions, the 348 (13.1%) asymptomatic patients, 164 (6.2%) patients without viable myocardium in the CTO territory, and 306 (11.5%) patients in whom the Synergy between PCI with Taxus and Cardiac Surgery Score II favored coronary artery bypass grafting (CABG) had higher 5‐year death or MI compared with the rest patients in each category (12.0% vs. 8.6%, p = .04; 16.3% vs. 8.5%, p  < .0001; 12.2% vs. 8.6%, p = .03), respectively. Multivariable regression analysis demonstrated that without symptom (hazard ratio: 1.51; 95% confidence interval: 1.06–2.15; p = .02), non‐viable myocardium in CTO territory (hazard ratio: 1.77; 95% confidence interval: 1.16–2.72; p = .009), and deemed more favorable for CABG (hazard ratio:1.54; 95% confidence interval: 1.04–2.28; p = .03), but not the technical success (hazard ratio:0.85; 95% confidence interval: 0.62–1.18; p = .34), were independent predictors for the primary endpoint. Conclusions: In this large cohort of CTO‐PCI, those who were asymptomatic, non‐viable myocardium in the CTO territory, or deemed more favorable for CABG were associated with higher risk of long‐term mortality or MI.